Peningkatan Nilai Guna Limbah Jeans Melalui Metode Upcycle Sebagai Peluang Usaha Kreatif Berkelanjutan - Erika Hartati Tampubolon; Nerinda Ingrayani saragih; Fandra Dikhi Januardani; Yusmalinda (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to raise environmental awareness and empower Gen Z by utilizing jeans waste into valuable products using the upcycling method at the Eben Ezer Village Hall, Sinaksak Village, Pematang Siantar City. The main problem faced is the increase in textile waste due to the fast fashion trend. This program uses a Participatory Action Research (PAR) approach with Gen Z as its partner. The results of this community service activity indicate an increase in Gen Z's awareness and concern about the impact of textile waste on the environment. The direct output of this program is the creation of bags and hair clips from used jeans that have aesthetic value and economic potential, and an increase in Gen Z's knowledge. Thus, this upcycling-based community service program not only provides solutions to environmental problems but also opens up sustainable creative business opportunities for the younger generation.